Rozległa torbiel zapalna żuchwy u 6-letniej pacjentki - opis przypadku = Extensive inflammatory cyst of the mandible in a 6-year old patient - case report - Aleksandra Szczepkowska; Małgorzata Lipczyńska; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2016)
Szczepkowska Aleksandra, Lipczyńska Małgorzata, Osica Piotr, Janas-Naze Anna. Rozległa torbiel zapalna żuchwy u 6-letniej pacjentki - opis przypadku = Extensive inflammatory cyst of the mandible in a 6-year old patient - case report. Journal of Education, Health and Sport. 2016;6(12):582-592. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.217557 http://ojs.ukw.edu.pl/index.php/johs/article/view/4102         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 20.12.2016.       Rozległa torbiel zapalna żuchwy u 6-letniej pacjentki - opis przypadku Extensive inflammatory cyst of the mandible in a 6-year old patient - case report   Aleksandra Szczepkowska1, Małgorzata Lipczyńska2, Piotr Osica1, Anna Janas-Naze1       1 Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze 2 Studenckie Koło Naukowe przy Zakładzie Chirurgii Stomatologicznej UM w Łodzi         Adres do korespondencji: Aleksandra Szczepkowska Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: aleksandra.szczepkowska@gmail.com tel. 42 675 75 71               Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001   Streszczenie: W pracy opisano przypadek leczenia jednoetapowego rozległej torbieli zapalnej żuchwy u 6-letniej pacjentki, przeprowadzonego w znieczuleniu ogólnym. Słowa kluczowe: torbiel zapalna, znieczulenie ogólne, metoda jednoetapowa       Abstract: The article presents the case of large inflammatory cyst of the mandible in a 6-year old patient, treated in general anaesthesia. Key words: inflammatory cyst, general anaesthesia, one-step method